2023
DOI: 10.2196/41892
|View full text |Cite
|
Sign up to set email alerts
|

Alarming Trends of Cesarean Section—Time to Rethink: Evidence From a Large-Scale Cross-sectional Sample Survey in India

Abstract: Background Cesarean section (CS) delivery rate has increased significantly both globally and in India, thereby posing a burden on overstretched health systems. Objective This study plans to understand the factors associated with CS rate with an objective to (1) analyze the trends of CS delivery from 1998-99 to 2019-21 and (2) understand the proximate determinants of CS deliveries in India. Methods Analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
4
5
0
Order By: Relevance
“…This study found an association between level of education and likelihood of CD, with higher education levels conferring reduced risk. These findings are in line with other studies showing that a high level of maternal education is associated with a lower risk of CD [9, 15]. However, the reason for this association is unknown.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study found an association between level of education and likelihood of CD, with higher education levels conferring reduced risk. These findings are in line with other studies showing that a high level of maternal education is associated with a lower risk of CD [9, 15]. However, the reason for this association is unknown.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the risk of CD was decreasing with maternal education but increases with higher wealth status and in women giving birth in private healthcare facilities. Similar findings have been made in previous studies [9,15,20,30]. Maternal age was not associated with CD, which contrasts with findings from other publications [31][32][33].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The adjusted odds ratio underscores a substantial association between the place of delivery and the possibility of undertaking a CS. This nding aligns with global trends where private health facilities often witness higher rates of cesarean sections (42), which may be in uenced by the perceived convenience of scheduled deliveries (43), patient demands (43)(44)(45), and potential nancial considerations (28,38,40).…”
Section: Discussionsupporting
confidence: 66%